Activity Antibacterial Extract Ethanol Duku (Lansium domesticum Corr) to Bacteria Salmonella typhi - Afifah Zahra Indahsari Nasir; Reynatha C.A. Pangsibidang (Health Research Journal of Indonesia, 2026)
Indonesia is currently among the countries with the highest incidence of typhoid fever, and research suggests that langsat fruit extract may inhibit the spread of Salmonella Typhi. Typhoid fever is a systemic infection caused by the bacterium Salmonella enterica subspecies enterica serovar Typhi (Salmonella Typhi) and is an important cause of illness and death worldwide, with an estimated 10.9 million new infections and 116,800 deaths. Objective: This study aims to determine the antibacterial activity of the ethanol extract of langsat fruit peel against Salmonella typhi by reviewing related articles. Method: This literature review uses a descriptive approach, examining several studies published in journals and scientific articles on the antibacterial activity of langsat ethanol against Salmonella Typhi. The databases used are Google Scholar and Scopus, with a time span of the last 10 years. Results: In this study, antibacterial activity against Salmonella Typhi was observed at concentrations of 25%, 50%, and 75%. The average diameters of the inhibition zones are 10.22mm, 11.94mm, and 13.63 mm. The concentration with a strong inhibition zone is 75%, which has greater antibacterial activity compared to concentrations of 50% and 25%. This is due to the presence of secondary metabolite compounds, including alkaloids, flavonoids, saponins, tannins, and triterpenoids. Conclusion: Experimental research shows that langsat fruit peel extract has potential as a natural solution for inhibiting Salmonella Typhi.